LEXICAL SEMANTIC REPRESENTATION OF ENGLISH LEGAL TERMS - Vakhidova Feruza Muhammadjonovna (Scholar Express Journal, 2023)
This article is based on the lexical semantics of legal terms in English. The article describes the specific aspects of the lexical semantic representation of these terms. The main problems encountered in this regard are also emphasized
Keywords: polysemy; synonymy; linguistics